Chronic Gingivostomatitis with Esophagitis in Cats. (27th September 2017) - Kouki, M.I.; Papadimitriou, S.A.; Psalla, D.; Kolokotronis, A.; Rallis, T.S.
Abstract : Background: Chronic gingivostomatitis in cats (FCG) is a debilitating disease with potentially deleterious effects on overall health. Hypothesis/Objectives: Little is known about the pathophysiology and overall impact of FCG. The aims of our study were to investigate whether gingivostomatitis occurs concurrently with esophagitis, if FCG treatment contributes to esophagitis and if esophagitis exacerbates signs of FCG. Animals: Fifty‐eight cats with clinical signs of FCG and 12 healthy control cats exhibiting no signs of oral disease, all client‐owned. Methods: Prospective study. Physical, oral and endoscopic examinations were performed on all cats. Measurements of salivary and esophageal lumen pH were obtained from both groups. Biopsies were acquired from sites of esophageal inflammation in cats with FCG and from normal‐appearing esophageal mucosa in control cats. Results: The majority of cats with clinical signs of FCG exhibited some degree of esophagitis especially in the proximal (44/58) and distal (53/58) parts ( P < 0.001) with or without columnar metaplasia, compared to controls. All cats lacked signs related to gastrointestinal disease. Salivary and esophageal lumen pH were not statistically different compared to controls. Conclusions and Clinical Importance: Feline chronic gingivostomatitis seems to occur concurrently with esophagitis. Esophagitis also should be managed in cats with chronic gingivostomatitis because it may aggravate the existing condition.